Peran Guru Pendidikan Agama Islam Dalam Meningkatkan Literasi Keagaman Siswa SMP Islam Asyafi'iyah Batealit Jepara - Baihaqi Khakim; Fathur Rohman (Universitas Islam Lamongan, 2026)
The low religious literacy among students becomes one of the challenges in Islamic education, especially in shaping a strong religious character. In this situation, Islamic Education (PAI) teachers have a very important role in instilling Islamic values and guiding students to be able to understand and practice Islamic teachings thoroughly. This study aims to examine the role and strategies of PAI teachers in improving students' religious literacy at SMP Islam Asyafi’iyah Batealit Jepara. This study uses a descriptive qualitative approach. Data collection was conducted through observation, interviews, and documentation. The data analysis process refers to the Miles and Huberman model, which includes stages of data collection, data presentation, and conclusion drawing. The results of the study show that PAI teachers act as educators, mentors, facilitators, as well as role models for students. The strategies implemented include the habituation of reading Asmaul Husna every morning, weekly memorization of the 30th Juz of the Qur'an, performing Dhuha sunnah prayer in congregation and obligatory Dhuhur prayer in congregation, holding istighosah activities together, implementing contextual learning, and utilizing the school library facilities. Supporting factors for the success of this program include the creation of a religious culture in the school environment and the existence of a pesantren program. However, there are some obstacles such as limited religious reading materials and low student interest in reading religious literature.